Mitral regurgitation in heart failure: insights from CPET combined with exercise echocardiography. (18th May 2016) - Bandera, Francesco; Generati, Greta; Pellegrino, Marta; Garatti, Andrea; Labate, Valentina; Alfonzetti, Eleonora; Gaeta, Maddalena; Castelvecchio, Serenella; Menicanti, Lorenzo; Guazzi, Marco
Abstract : Aims: In heart failure patients with reduced ejection fraction (HFrEF), exercise-induced functional mitral regurgitation (MR) may affect functional capacity and outcome. We sought to study functional and cardiac phenotypes of HFrEF patients according to the MR degree. Methods and results: We performed rest and exercise echocardiography (Ex-Echo), simultaneously combined with cardiopulmonary exercise test (CPET), in 102 HFrEF patients, identifying 3 groups: non-severe (ERO <20 mm 2 ) MR (group A), exercise-induced severe (ERO ≥20 mm 2 ) MR (group B), and rest severe MR (group C). Patients were tracked for the composite end point of death and heart failure hospitalization. Group B (ERO: rest= 14 ± 5 mm 2, Ex= 28 ± 6 mm 2 ; P = < 0.001) had a functional impairment (workload = 56 ± 21 vs. 50 ± 17 watts, P = 0.42; peak VO2 = 11.8 ± 3.2 vs. 11.5 ± 3.0 mL/Kg/min, P = 0.70) similar to Group C (ERO: rest = 29 ± 7 mm 2, Ex = 42 ± 7 mm 2, P = < 0.001), associated with comparable advanced left ventricle remodelling (end diastolic indexed volume = 107 ± 34 vs. 115 ± 30 mL/m 2, P = 0.27), characterized by exercise-induced pulmonary hypertension (PH) (Ex systolic pulmonary pressures = 63 ± 16 mmHg). Group C showed the worse cardiac phenotype (right ventricle dilatation, dysfunction, and rest PH) with severe ventilatory impairment (VE/VCO2 = 41.2 ± 11) compared with Groups A and B. Moreover, Group C had the higher rate of death and HF hospitalization. Conclusions: In HFrEF patients, severe dynamic MR produces functional limitation similar to rest severe MR, characterized by dynamic PH. Rest severe MR reflects the most advanced bi-ventricular remodelling associated with rest PH, the most unfavourable ventilatory profile, and the worst mid-term outcome.